Individualized activity recommendation based on a physical fitness assessment increases short- and long-term regular physical activity in people with multiple sclerosis in a retrospective cohort study - van der Ven, Eva; Patra, Stefan; Riemann-Lorenz, Karin; Kauschke, Katrin; Freese-Schwarz, Katrin; Welsch, Götz; Krause, Nicole; Heesen, Christoph; Rosenkranz, Sina Cathérine (Frontiers in Neurology, 2024)
Background: Despite the evidence of beneficial effects of physical activity (PA), people with multiple sclerosis (pwMS) are less physically active than the general population. To increase PA in pwMS, we developed a structured individually tailored PA promotion program which is conducted within clinical practice in a university-based outpatient clinic since 2016. This study serves as retrospective quality control of this program. Objective: In a retrospective cohort study, we assessed the physical fitness of pwMS and the impact of the program on short- and long-term PA changes and behavioral determinants. Methods: The program consisted of four appointments each two to four weeks apart. Spiroergometric test results of female pwMS were compared to female non-MS controls who underwent a voluntary physical fitness analysis. The short version of the Freiburger questionnaire, self-developed questions and the modified Physical activity screening questionnaire (PASQ) were sent to all participants assessing the PA levels before the program, three months after the program (short-term), and at the time of the survey (long-term). Additionally, established questionnaires assessed behavioral determinants before the program and long-term. Results:166 participants (mean age 38,32(± 10,61 SD),mean EDSS 2.30(±1.29 SD) and mostly females(63,3%, n=105) were included in the study and started the program.136 participants completed the program. Out of these 52.4%(n = 87) answered the questionnaires in 12.38(±11.34 SD)months after finishing the program. At baseline female pwMS (n=100) showed a lower physical fitness in comparison to non-MS controls (n=26) (maximal workload (Watts):138.86±37.85 vs. 191.73±45.25, p < 0.001; peak oxygen consumption (ml min–1 kg–1):26.40±7.23 vs. 31.56±10.10, p = 0.020).pwMS were more regularly active in short-(62.1%)and long-term(55.2%) compared to baseline(24.2%, p < 0.001).Among the activated participants, we observed improved internal motivation(p = 0.002)and decreased perception of barriers(p = 0.006) compared to baseline. Conclusion: PwMS showed a lower physical fitness in comparison to non-MS controls. An individually tailored PA promotion program might improve behavioral determinants and thereby increase short- and long-term PA levels of pwMS.